Engaging Black men in college through leadership learning - Beatty, Cameron C.; Ford, Jesse R. (Contemporary perspectives on leadership learning., 2023)
"This book is intended to be a practical and scholarly resource to aid in the awareness of Black men in college, Black men's leadership identities and experiences, and the growing need to assist this population's success in college and beyond. Engaging Black Men In College Through Leadership Learning centers on leadership and Black identity as it tackles the intersecting identities of maleness, Blackness, and leadership identity as it encourages educators to consider the importance of the college environment in shaping the next generation of Black men collegiate leaders. In addition, this scholarship provides insight into Black men's leadership experiences in various contexts - including fraternity life, first-year experiences, and student organizations, while capturing the collective experiences of Black men as leadership learners at different types of institutions, including HBCUs, Community Colleges, PWIs and a host of other institution types. This resource is for leadership educators and practitioners to develop Black men as leaders on today's college campuses, where our global society continues to navigate challenges. This book also situates more nuanced topics such as mental health, trans identity, graduate education, and the experiences of former foster care youth, which provides insight into the experiences of Black men as leaders on college campuses. These contexts illustrate the need to see Black men's leadership as a critical, dynamic, and ever-evolving component on college campuses that requires intentionality to best develop, serve, and holistically engage Black men in leadership learning. We encourage readers of this text to consider how black men's experiences with leadership are woven into the fabric of your college campus and how you can be an advocate for more critical and sustainable ways to engage Black men in college through leadership learning"--